Studies in chromium complexes - Friend, Maurice Temple (Rhodes University, Faculty of Science, Department of Chemistry, 1953)
In this work physical and analytical methods have been used to investigate the potassium salts of certain dioxalato chromium (III) complexes. The solid potassium salts of the trioxalatochromiate and the cis and trans dioxalatodiaquochromiates together with a salt corresponding to potassium dioxalatosulphatoaquochromiate were prepared. The mono- and dihydroxo derivatives of the cis and trans dioxalatochromiates were also obtained in aqueous solution. The methods of preparation and analysis used are described. Spectrophotometric absorption curves obtained on solutions of these salts using a Beckman Spectrophotometer are in agreement with results of previous workers, and the new absorption curve obtained from a solution of the solid cis dioxalatodiaquochromia salt shows that it is pure and gives additional proof of the completeness of the trans - cis isomerisation. Summary, p. i.
Keywords: Complex ions; Chromium